2012
DOI: 10.1111/j.1600-9657.2012.01123.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mouthguards on the athletic ability of professional golfers

Abstract: The purpose of this study was to determine the effect of stabilization splints and mouthguards on the athletic ability of professional golfers. For this study, eight professional golfers with a mean age of 20.5 were selected. These participants performed four trials of 10 driver swings and 10 putts with or without a stabilization splint (control group) or mouthguard. For the 4th trial, the splints were adjusted using a simple blind test so that the participants were unaware of the unilateral molar contact. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
3

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 16 publications
(21 reference statements)
0
28
0
3
Order By: Relevance
“…To control variables associated with occlusal position, we designed protocols to maintain mandibles in a fixed position with 2 mm increase in vertical dimension from the midpoint of the line connecting the deepest gingival points of canines and premolars. While the vertical position of the mandible most likely to confer systemic effects has been known unclear and even considerably variable over individuals, vertical increase of 2 mm is frequently used by several studies on the fabrication of mouthguards, corresponding the range of freeway space 11,29. Moreover, Chakfa et al reported that when gradually increasing the vertical dimension from ICP, maximum increases in cervical flexors and deltoid muscular strength were obtained in the 2 to 12 mm range of vertical dimension 11.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To control variables associated with occlusal position, we designed protocols to maintain mandibles in a fixed position with 2 mm increase in vertical dimension from the midpoint of the line connecting the deepest gingival points of canines and premolars. While the vertical position of the mandible most likely to confer systemic effects has been known unclear and even considerably variable over individuals, vertical increase of 2 mm is frequently used by several studies on the fabrication of mouthguards, corresponding the range of freeway space 11,29. Moreover, Chakfa et al reported that when gradually increasing the vertical dimension from ICP, maximum increases in cervical flexors and deltoid muscular strength were obtained in the 2 to 12 mm range of vertical dimension 11.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the effects of intraoral appliances, including the effect of mouthguards on physical performance might be due to a change in condylar position,36 a horizontal or a vertical mandibular shift,26 or a change in the distribution of occlusal force 29,37. In a previous study on the effects of the even distribution of occlusal force, it was found that unilateral occlusion or disharmony in the left and right masticatory muscles led to deviations of cervical vertebrae 38.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ont montré que le port de protège-dents de performance, réalisés selon les principes de la dentisterie neuromusculaire ou des dispositifs MORA, permettait d'améliorer les performances musculaires [3,4,16,17,[53][54][55] que ce soit en termes de :…”
Section: Approche Commune (Neuromusculaire Et Posturale)unclassified
“…In this context, recent studies investigated the performance of golf professionals while using stabilizing splints. Whereas Egret et al (2002) observed significant reductions in ball speed variability but no changes in average ball speed and kinematic pattern of the golf swing, Kwon et al (2010) and Pae et al (2013) observed significant improvements in driving distance and club head speed when the oral appliances were being used. Because accurate hitting of the ball and transfer of as much momentum as possible to the ball are important aspects of improving one’s driving distance ( Hume et al, 2005 ), it was suggested that the improvements were induced by increased focus of attention at the moment of impact and/or increased muscle strength in the upper and lower extremities.…”
Section: Introductionmentioning
confidence: 96%